Assassination of the Duke Louis of Orleans on Vieille du Temple Street on 23 November 1407 - O. I. Nuzhdin (Научный диалог, 2017)
The problem of the outbreak of civil war in the French Kingdom in the early 15th century is studied. The author mentions the struggle for power in the government between two relatives of king Charles VI, Duke Louis of Orleans and Duke Jean the Fearless, as one of prerequisites. Their confrontation ended with the assassination of the Duke of Orleans on 23 November 1407. The article examines in depth the course of the investigation, which was conducted by the Provost of Paris, with the result that just in two days the circle of persons involved in the commission of the crime was defined, and the Duke of Burgundy was called the main suspect in its organization. On the basis of a wide range of sources the author has demonstrated the methodology of investigation in the Middle Ages. It is noted that it was quite effective for its time. Special attention is paid to the analysis of the reasons that pushed the Duke of Burgundy for the murder. The novelty of the research is seen in the fact that the author considers the opinion of modern researches about the exclusively political motives of the crime insufficiently reasoned. The article also shows the fates of the participants in the crime, including the Duke of Burgundy, who was murdered in Montero in 1419.